2015
DOI: 10.5141/ecoenv.2015.019
|View full text |Cite
|
Sign up to set email alerts
|

Gap formation and susceptible Abies trees to windthrow in the forests of Odaesan National Park

Abstract: Extremely strong winds and heavy rainfall caused canopy gaps in a mixed Abies holophylla broadleaf forest and a Quercus mongolica-dominated forest in Odaesan National Park, Korea in October 2006. The impact of the combination of strong winds and torrential rain on the development of forest gaps and canopy structures were investigated. The mean size of newly created gaps were 205 m 2 in the mixed forest and 86 m 2 in the Quercus forest, and were created by 2.8 and 1.4 gapmaker trees, respectively. Among the 73 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Addition, it was indicated that previous studies have indicated that the risk of windthrow damaged typically increases with tree age and younger stands with shorter and more flexible trees tend to be less susceptible to windthrow (Atay, 1987;Moore, 2000). Nevertheless, in shallowrooted species, particularly in areas with high storm intensity and poor soil structure, windthrow damage can be more prevalent than expected (Jeon et al, 2015).…”
Section: Results On Statistical Analysesmentioning
confidence: 97%
“…Addition, it was indicated that previous studies have indicated that the risk of windthrow damaged typically increases with tree age and younger stands with shorter and more flexible trees tend to be less susceptible to windthrow (Atay, 1987;Moore, 2000). Nevertheless, in shallowrooted species, particularly in areas with high storm intensity and poor soil structure, windthrow damage can be more prevalent than expected (Jeon et al, 2015).…”
Section: Results On Statistical Analysesmentioning
confidence: 97%
“…Rooted traces by wild boar was very frequently found, suggesting an important role in the dynamics of the forest floor [52]. This would be somewhat similar to how the numerous pits formed by windblown function as microsites for seed germination and establishment [58][59][60]. The food source of wild boars varies according to season.…”
Section: Introductionmentioning
confidence: 85%
“…The secondary keyword in terms of burst strength is "impact". Some articles have discussed the impact of forest gaps on the community in gaps [7], and others have discussed the impact of disturbance on gap formation [61]. The third keyword in terms of burst strength is "mortality."…”
Section: Discussionmentioning
confidence: 99%